SOCIALIZATION OF AEROBIC EXERCISE BASED ON CULTURE IN SOUTH SULAWESI - Poppy Elisano Arfanda; Ians Aprilo; Arimbi, Arimbi; Nurliani, Nurliani; Wahyana Mujari Wahid (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The socialization of aerobic dance based on South Sulawesi culture was raised because of the increasing dependence of humans on technology so that physical activity is reduced. This community service activity focuses on encouraging physical activity, especially sports, in this case aerobic dance based on South Sulawesi culture. This service activity aims to provide sports references to teenagers aged 17-25 years. The form of South Sulawesi culture that is carried out in aerobic dance is in the form of several movements and music adopted from dances in South Sulawesi. Before and after implementing the South Sulawesi culture-based aerobic dance, participants had their pulse measured to see their resting pulse. Measure their pulse using an oximeter. The results showed an increase between the resting pulse rate and the training pulse rate for all subjects entering the training zone